Pemberdayaan Ibu-Ibu Kelompok Nelayan melalui Pengolahan Hasil Tangkapan Ikan di Kelurahan Lowu-Lowu - Ernawati Malik; Waode Adriani Hasan; Tri Astuti; Muhammad Rais R.; Ameliyani Kusi (UNUSA Press, 2022)
One strategy in empowerment to increase people's income is creating new entrepreneurs. Lowu-Lowu village is one of the urban villages located in Baubau City. The village's geographical location on the coast has promising potential for fishery resources. In addition, 14% of the 2,414 population in the Lowu-Lowu village live as fishers. So far, fishers in the Lowu-Lowu sub-district did not process fish caught into fish processed products. Fishers sold their fish directly to village markets or markets in other areas in Baubau City, so there was no additional income for fishers. The partner's issue was a lack of knowledge among women in the Lowu-Lowu village to start a home business. Therefore, this community service team held seminars regarding entrepreneurship and training regarding processing fish products to empower women in the Lowu-Lowu village. So they can make extra money for fishers' families. The participants were wives of the Lowu-Lowu fishers group and women of the Lowu-Lowu Family Welfare Empowerment. This activity resulted in increased success indicators before and after community service. In conclusion, community service through empowerment positively impacted women in the Lowu-Lowu village, particularly creating insight (knowledge and perception) regarding entrepreneurship and encouraging entrepreneurial behaviour. The following community service activities could give training on creating business profiles and accounting records for firms